ANALISIS PENGARUH PEMBERDAYAAN, PELATIHAN, DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI DENGAN MEDIASI MOTIVASI KERJA (STUDI PADA DINAS PENDIDIKAN KABUPATEN REMBANG) - Khamidah, 11.42.02.0138 (Jurnal Mahasiswa Pasca Sarjana, 2014)
Improved performance at the District Education Office employee Apex, plagued by a variety of factors that empowerment is very minimal, less training and career development is not open, how the employee can improve and enhance the quality of work. The purpose of this study to know the effect of empowerment, training and career development of employees at the District Education Office Apex. The research was conducted on the District Education Office employee Apex as much as 128 people. Sample taking the entire population for the research sample. Data analysis using matrix component test the validity, reliability test with alpha Crombach, multiple regression analysis, t test and test with an adjusted r square R2. Results reveal that empowerment does not affect on employee motivation. Positive and significant effect of training on employee motivation. Career Development positive and significant impact on employee motivation. Empowerment positive and significant effect on employee performance. Positive and significant effect of training on employee performance. Career Development positive and significant positive effect on employee performance. Motivation is not mediate the effect of empowerment on employee performance. Motivation is not mediate the effect of training on employee performance. Motivation is not mediate the effect of career development on employee performance. Keywords: Empowerment, Training, Career Development, Motivation and Performance